Factors Relating to the Success of the Health Information System at the Buton District Health Center - Dilla, Sitti Marni; Tasnim, Tasnim; Amraeni, Yunita; Selviana, Arizka (Magister Kesehatan Universitas Mandala Waluya, 2022)
29 Introduction: Program planning that has been carried out so far has not been carried out according to procedures due to inadequate human resources; organizing; Cooperation and Coordination; strengthening of data sources; management of data on utilization and development of resources, operation of the Electronic Health System; development of Health Information System; weak monitoring and evaluation; and there is no coaching and supervision. The purpose of the study was to determine the factors related to the success of the health information system at the health center in the Buton district. Method: This type of research is quantitative using a cross-sectional study design. This research has been carried out from January to February 2022. The population is all officers who are considered to have a role and responsibility for health services in the Buton district. with a total of 579 health workers in the Buton district who work at the Health Center, with a sample of 90 respondents using the Simple Random Sampling technique. Result: Study found that there was a relationship between planning, organizing, cooperation, and coordination factors, strengthening data sources, data management, resource utilization and development, electronic system operation, monitoring, and evaluation of the Health Information System at the Buton District Health Center. Conclusion: It is suggested the importance of monitoring and evaluating the readiness of the Health Center in implementing a more optimal Health Information System based on the completeness of the infrastructure, adding human resources according to the field.